IMPACT OF STRATEGIC PLANNING ON ORGANISATIONAL GROWTH IN THE NIGERIA MANUFACTURING SECTOR - Orishede, Felix (African Journal of Social and Behavioural Sciences, 2020)
The study focuses on strategic planning, implication for organizational growth in the Nigeria manufacturing sector with the following specific objectives. To ascertain the impact of strategic planning on organizational profitability, to assess the extent to which strategic planning affects the market share of organizations, to examine the effect of strategic planning on organization product growth and development. The study made use of primary data, the survey research design method was employed in this study, the stratified random sampling technique was used to select the sample size used in this study. A validated set of questionnaire was administered on randomly selected respondent drawn from the (5) organisations under study. Frequency distribution table and percentage methods were used for data presentation and analysis respectively while chi-square statistical tool was used for the test of the hypotheses formulated for the study. It was discovered that strategic planning has significant effect on organizational profitability, market share and product growth and development. The study concludes that Strategic planning aids organizational growth and performance. It was recommended that the process of strategic planning should be made as flexible as possible to engender easy change. Efforts should be consistently geared towards the reduction of the cost of carrying out strategic plans and environmental scanning so as to make it both effective and efficient.